In Bello Proportionality: Philosophical Reflections on a Disturbing Empirical Study. Issue 2 (3rd April 2022) - de Wijze, Stephen; Statman, Daniel; Sulitzeanu-Kenan, Raanan
ABSTRACT: A recent empirical study has argued that experts in the ethics or the law of war cannot reach reasonable convergence on dilemmas regarding the number of civilian casualties who may be killed as a side effect of attacks on legitimate military targets. This article explores the philosophical implications of that study. We argue that the wide disagreement between experts on what in bello proportionality means in practice casts serious doubt on their ability to provide practical real-life guidance. We then suggest viewing in bello proportionality through the prism of virtue ethics.